Spatial and biogeographic characterization of macroalgal assemblages from Bahía del Rincón, Baja California Sur, Mexico. - Riosmena-Rodríguez, R (2005)
Macroalgal studies in Baja California Sur have dealt mainly with occurrence and seasonality, but some areas are poorly known even for these basic data. Bahía del Rincón-La Rivera is an important high-productivity fisheries area where coastal infrastructure development is under way. A spatial characterization of the marine flora from Bahía del Rincón-La Rivera was done by intensive sampling at different depths and localities with skin and SCUBA diving. At least 500m2 were surveyed in each site. Additionally, quantitative sampling was done in ten random 25 cm2 quadrates per site. In the intertidal section, density and cover estimates were used. We also investigated the historical records and geographical affinities. A total of 72 species were identified (most were red algae: 62%). We found no general trend in the biogeographical affinities, which varied with each taxonomic group. Most brown algae species were tropical-endemic; red algae temperatecosmopolite and green algae tropical-cosmopolite. In the spatial assemblage structure we found a high similarity between the intertidal areas, but a low similarity in shallow or deeper areas (3-5 m). This pattern was the same when we compared the abundance of the main species. We suggest that there are significant spatial differences in recruitment and development of the assemblages in relation to vertical distribution (depth) and position along the shore. There is a clear-cut Gelidium-Jania belt in the intertidal zone and a Padina-Dictyota belt below the low tide. Sporadic and year-round species occur in the intertidal zone, annual and perennial species below the low tide line. Sites differ in recruitment and this affects the abundance of other species (such as coraline and Caulerpa species). Temperature and sedimentation affect seasonality, but community structure is relatively constant throughout the year.